Problem Minimnya Minimnya Pengambilan Pembiayaan di Perbankan Syariah: Studi Kasus UMKM Furniture di Kabupaten Sumenep - Rafiqi, Iqbal; Jazuli, M Naufal (Assyarikah: Journal of Islamic Economic Business, 2024)
Sharia banking has a vital role in supporting economic progress in society, especially business actors such as MSMEs. However, not all MSMEs respond productively to the financing issued by Sharia banks, such as furniture MSMEs in Karduluk Village, Sumenep Regency, which still rarely utilize financing products from Sharia banks. This research aims to identify the problem of the lack of interest of Furniture MSMEs in Karduluk village in taking out Sharia Banking financing. This research uses a qualitative approach with a field study type of research. The data collection methods used were interviews, observation, and documentation. Analysis reduces data, presents the data, then concludes the data that has been presented. The subjects of this research were taken from Furniture MSMEs in Karduluk Village. The results of this research provide data that the interest of MSME furniture players in Karduluk village, Sumenep in choosing Sharia banking financing products is still relatively low. This is evident from the 30 informants that researchers interviewed, there are only 3 MSME players who carry out financing at sharia banks. The reasons are different, such as lack of promotion from Islamic banks or it is easier to borrow funds from relatives.